The evaluation of the research on the microbial fuel cells: A scientometric approach - Konur, Özcan (SILA SCIENCE, 2012)
The present study explores the characteristics of the literature on the Microbial Fuel Cells (MFCs) published during the last three decades based on the Science Citation Index Expanded (SCIE) and its implications using the scientometric techniques. The results of this study reveal that the research output on the MFCs has grown exponentially during this period with 1,185 papers in total with paralleling enormous changes in the research landscape. Papers mostly have been journal articles, reviews, and proceedings papers, published predominantly in English. The US, China, and South Korea have been the tree most prolific countries. The "Penn State Univ" has been the most prolific institution and "Logan BE" of the US has been the most prolific author. "Bioresource Technology" has been the most prolific journal publishing 10.4% of the research output on the MFCs whilst, "Biotechnology & Applied Microbiology" has been the most prolific subject area covering 38.6% of the research output. There have been 24,743 citations with 20.88 citations per paper and "H-index" of 79. "Logan BE et al." [1] has had the highest impact on the literature with 514 citations and 85.7 citations per year. Both the research output and the citations have increased spectacularly after 2004 making a respective peak in 2010. The results of this first-ever full scientometric study of its kind for the MFC research show that the scientometric analysis has a great potential to gain valuable insights into the evolution of the high-profile edge-cutting research on the MFCs, complementing other research techniques such as literature reviews, meta-analysis, and content analyses as well as complementing the scientometric research on the other types of renewable energies such as bioenergy and biohydrogen.
Keywords: Microbial Fuel Cells (MFCs); Bioenergy; Research evaluation; Scientometrics; Web of Knowledge